Predictors of therapy resistant asthma: outcome of a systematic evaluation protocol. Issue 7 (1st July 2003) - Heaney, L G; Conway, E; Kelly, C; Johnston, B T; English, C; Stevenson, M; Gamble, J
Abstract : Background: It has been suggested that asthmatic subjects with persisting symptoms despite adequate maintenance therapy should be systematically evaluated to identify factors contributing to poor control. The aims of this study were to examine the prevalence of these factors in a cohort of sequentially referred poorly controlled asthmatics, and to determine if any factor or combination of factors predicted true therapy resistant asthma (TRA). Methods: Patients were evaluated using a systematic evaluation protocol including induced sputum analysis, psychiatric assessment, ear, nose and throat examination, pulmonary function testing, high resolution CT scan of the thorax, and 24 hour dual probe ambulatory oesophageal pH monitoring; any identified provoking factor was treated. Asthma was managed according to BTS guidelines. Results: Of 73 subjects who completed the assessment, 39 responded to intervention and 34 had TRA. Subjects with TRA had a greater period of instability, a higher dose of inhaled steroids at referral, more rescue steroid use, and a lower best percentage forced expiratory volume in 1 second (FEV1 %). Oesophageal reflux, upper airway disease, and psychiatric morbidity were common (57%, 95%, 49%, respectively) but were not more prevalent in either group. Using multivariate logistic regression analysis, inhaled steroid dose >2000 μg BDP, previous assessment by a respiratory specialist, and initial FEV1 % of <70% at referral predicted a final diagnosis of TRA. Conclusions: In poorly controlled asthmatics there is a high prevalence of co-morbidity, identified by detailed systematic assessment, but no difference in prevalence between those who respond to intervention and those with TRA. Targeted treatment of identified co-morbidities has minimal impact on asthma related quality of life in those with therapy resistant disease.